Strengthening the Honest Character of Grade 3 Students at Madrasah Ibtidaiyah during the Covid-19 Period: Penguatan Karakter Jujur Siswa Kelas 3 di Madrasah Ibtidaiyah pada Masa Covid-19 - Puput Oktafiani; Akhtim Wahyuni (Academia Open, 2022)
This study aims to determine the teacher's strategy in providing strengthening the honest character of third grade students at MI Muhammadiyah 2 Kedung Banteng during the covid-19 period, to find out the obstacles faced by teachers in strengthening the honest character of third grade students at MI Muhammadiyah 2 Kedung Banteng during the covid-19 period. 19. This study uses a qualitative descriptive approach. The research subjects were the principal, teachers, and students at Mi Muhammadiyah 2 Kedung Banteng. This study uses data collection techniques in the form of observation, interviews, and documentation. Data analysis used steps of data reduction, data presentation, and drawing conclusions. The validity of the data using triangulation of data sources and techniques. The results showed that the strategy used by the teacher to implement character education in the teaching and learning process in the classroom was by being an example for students and teaching moral values ​​in each lesson. There are 4 inhibiting factors in efforts to build the character of third grade students at MI Muhammadiyah 2 Kedung Banteng. Limited time, Lack of attention from parents of students, Influence of the surrounding environment, Lack of communication. Highlights: Teacher as a role model: The teacher's strategy involves being an example for students and imparting moral values in every lesson, fostering honesty in third-grade students. Inhibiting factors: Limited time, lack of parental involvement, influence of the surrounding environment, and lack of communication pose obstacles in strengthening the honest character of third-grade students during the Covid-19 period. Qualitative descriptive approach: The study utilizes a qualitative descriptive approach, employing observation, interviews, and documentation as data collection techniques to understand the teacher's strategies and challenges in character education. Keywords: Teacher strategy, Honest character, Third-grade students, Covid-19 period, MI Muhammadiyah 2 Kedung Banteng